PENGARUH DISIPLIN KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN KABUPATEN LABUHANBATU UTARA - Yuniman Zebua (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
This research was conducted to determine the effect of work discipline and workload on employee performance at the North Labuhanbatu regency of Agriculture. The method used in data collection in this study is through a questionnaire method using total sampling method to determine the respondent's response to each variable. While the data analysis technique used is multiple linear regression and hypothesis testing using the t test to test the partial regression coefficient and the F test to test simultaneously. In this study, the regression equation Y = 1,772+ 0.237X1 + 0.422X2 was obtained. The results of this study indicate that the variables of Work Discipline and Workload either partially or simultaneously have a positive and significant effect on employee performance. Judging from the test results the coefficient of determination ((R2) shows the magnitude of the contribution of the influence of the independent variables on the dependent variable, the results show the value of R2 = 0.434 which means that 43.4% of employee performance is influenced by Work Discipline and Workload while the rest is 56.6%. influenced by other variables not studied.